Pragmatic markers resulting from language contact. The case of sañani in Aymara - Quartararo, Geraldine (Onomázein, 2020)
This paper explores the pragmatic functions of a previously unattested pragmatic marker (Fraser, 1996, 2006) found in Aymara, i.e. sañani ‘let’s say’. The uses of sañani suggest that this marker is the result of the influence of Spanish on Aymara due to sustained language contact. Sañani seems to be the “replication” (Heine and Kuteva, 2005) of the Spanish pragmatic marker digamos ‘let’s say’. Like digamos (Grande Alija, 2010; Quartararo, 2017a), sañani functions as a pragmatic marker by signaling either an inferential process or the semantic relation between two discourse segments. The original data used for this analysis was gathered through the Family Problems Picture task (San Roque et al., 2012), the Pear Story task (Chafe, 1980) and personal and traditional narratives. All the data transcripts were used to compile a novel corpus of Aymara.